DIRECT DETERMINATION BY NEUTRON REFLECTION OF THE STRUCTURE OF TRIETHYLENE GLYCOL MONODODECYL ETHER LAYERS AT THE AIR-WATER-INTERFACE - Lu, J; Thomas, R; Penfold, J; Flitsch, S (1993)
Neutron reflectivity with isotopic substitution has been used to determine directly the structure of triethylene glycol monododecyl ether adsorbed at the air-water interface. The surface excess has been measured from concentrations ranging from twice the critical micelle concentration (cmc) (=5.5 × 10-5 M) to one fiftieth the cmc. The results are in good agreement with those from surface tension measurements and show that the area per molecule tends to a limiting value of 36 Å2. The structure of the adsorbed layer has been determined at four concentrations: cmc, 0.2 cmc, 0.0545 cmc, and 0.0182 cmc. Two different methods of analysis of the data have been employed. One is the optical matrix method which fits a single structural model to the reflectivity profiles from a set of isotopic species at a given concentration and the other is a more direct approach based on the kinematic theory. The two methods give structures identical within experimental error. The variation of the thicknesses of the hydrocarbon chain region of the adsorbed layer and the region where solvent has a density less than its bulk value (approximately described as the head group region) and the relative locations of chain and water distributions across the surface with bulk concentration have been determined. For the saturated monolayer at the cmc the thickness of the chain region is found to be 20 ± 1 Å, that of the head group region to be 11 ± 1 Å, and that of the mean center to center distribution of chains and water to be 10 ± 1 Å. The number of water molecules associated with each surfactant molecule is 6. At the lowest concentration (0.0182 cmc) where the monolayer is at its most dilute, it is found that the thickness of the whole layer is 15 ± 1 Å, that of the head regions is 7 ± 1 Å, and the separation of the two distributions is 5 ± 1 Å, with the number of water molecules per surfactant now about 10. Comparison of these values with the width of the chain and solvent distributions shows that the immersion of the hydrocarbon chains in the water varies from about 25% at the cmc to 40% at 0.0182 cmc. © 1993 American Chemical Society.